2009
DOI: 10.1016/j.neuron.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neurons in the Drosophila Genital Tract Regulate Female Reproductive Behavior

Abstract: Females of many animal species behave very differently before and after mating. In Drosophila melanogaster, changes in female behavior upon mating are triggered by the sex peptide (SP), a small peptide present in the male's seminal fluid. SP activates a specific receptor, the sex peptide receptor (SPR), which is broadly expressed in the female reproductive tract and nervous system. Here, we pinpoint the action of SPR to a small subset of internal sensory neurons that innervate the female uterus and oviduct. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
342
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(355 citation statements)
references
References 40 publications
7
342
1
Order By: Relevance
“…In wild-type females, neuronal expression of mSP or SPR can mediate the postmating switch in ppk, fru and dsx neurons [16,21,22,24]. Now we wanted to assess whether SP switches female postmating behaviour also in SPR mutant females via these previously identified neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In wild-type females, neuronal expression of mSP or SPR can mediate the postmating switch in ppk, fru and dsx neurons [16,21,22,24]. Now we wanted to assess whether SP switches female postmating behaviour also in SPR mutant females via these previously identified neurons.…”
Section: Resultsmentioning
confidence: 99%
“…In both the central nervous system and PNS, dsx and fru are expressed in approximately 700 and approximately 2000 neurons, respectively, in characteristic patterns, while ppk is expressed exclusively in a subset of peripheral nervous system (PNS) neurons [21,24,[26][27][28]. Overlapping expression of these three genes has been identified in a subset of genital tract neurons that project to central areas of the brain suggesting that these neurons signal the presence of SP to higher order processing centres in the brain [21,22,24]. Dsx-expressing neurons in the abdominal ganglion (Abg) that project to the genital tract and the central brain are also involved in the SP response [22].…”
Section: Introductionmentioning
confidence: 99%
“…In studies on Drosophila ovulation, female postmating behavior, and male courtship or reproductive behavior (Hasemeyer et al, 2009;Lee et al, 2001;Monastirioti, 2003;Yang et al, 2009), abdominal peripheral neurons were observed to directly project to the abdominal ganglion to mediate diverse functions. Therefore, although it is not yet clear what functions the Grs are mediating in the multidendritic neurons and reproductive organs, it seems likely that the information sensed by the Grs in these organs is conveyed to the abdominal ganglion to be processed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on expression pattern, it seems likely that the neurons expressing these Grs could function in regulation of accessory gland secretion in males or regulation of ovulation in females. Also, female postmating behavior is regulated upon detection of male sex peptide by receptors in sensory neurons innervating the female genital tract (Hasemeyer et al, 2009;Yang et al, 2009), suggesting that Gr-expressing neurons innervating the reproductive organs may have similar functions. Although sex-specific expression was not observed for any of the Gr-GAL4 drivers, it seems plausible that second order neurons may confer specificity in relaying information to higher centers, similar to what has been proposed for Gr32a (Koganezawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At least for egg production and receptivity changes, SP acts through its receptor, sex peptide receptor (SPR), which is expressed in neurons throughout the body of the female (Yapici et al, 2008). Previous work found that a set of SPR þ neurons that innervate the female reproductive tract and express the genes pickpocket and fruitless are necessary and sufficient for these changes (Hasemeyer et al, 2009;Yang et al, 2009). In an interesting talk, Carolina Rezaval (University of Oxford) described how several of these essential neurons share circuitry with neurons expressing the sex determination gene, doublesex.…”
mentioning
confidence: 99%